European Society of Anaesthesiology guidelines on peri-operative use of ultrasound-guided for vascular access (PERSEUS vascular access). Issue 5 (May 2020) - Lamperti, Massimo; Biasucci, Daniele Guerino; Disma, Nicola; Pittiruti, Mauro; Breschan, Christian; Vailati, Davide; Subert, Matteo; Traškaitė, Vilma; Macas, Andrius; Estebe, Jean-Pierre; Fuzier, Regis; Boselli, Emmanuel; et al.
Abstract : N/A: Ultrasound for diagnostic and procedural purposes is becoming a standard in daily clinical practice including anaesthesiology and peri-operative medicine. The project of European Society of Anaesthesiology (ESA) Task Force for the development of clinical guidelines on the PERioperative uSE of Ultra-Sound (PERSEUS) project has focused on the use of ultrasound in two areas that account for the majority of procedures performed routinely in the operating room: vascular access and regional anaesthesia. Given the extensive literature available in these two areas, this paper will focus on the use of ultrasound-guidance for vascular access. A second part will be dedicated to peripheral nerve/neuraxial blocks. The Taskforce identified three main domains of application in ultrasound-guided vascular cannulation: adults, children and training. The literature search were performed by a professional librarian from the Cochrane Anaesthesia and Critical and Emergency Care Group in collaboration with the ESA Taskforce. The Grading of Recommendation Assessment (GRADE) system for assessing levels of evidence and grade of recommendations were used. For the use of ultrasound-guided cannulation of the internal jugular vein, femoral vein and arterial access, the level evidence was classified 1B. For other accesses, the evidence remains limited. For training in ultrasound guidance, there were no studies. The importance of proper training for achieving competency and full proficiency before performing any ultrasound-guided vascular procedure must be emphasised. Abstract : Supplemental Digital Content is available in the text